THE URGENCY OF A SEPARATION OF PROPERTY AGREEMENT IN MARRIAGE AS AN EFFORT TO CREATE A HARMONIOUS FAMILY - Lestari Lamindo Limbong; Henry Aspan; Dahlan (CV. RADJA PUBLIKA, 2025)
As science develops, public awareness of the importance of legal protection for themselves also grows rapidly. Likewise, legal protection for married couples. The existence of a separation of property agreement in a marriage is one effort to avoid conflicts related to property in a marriage bond, the less conflict there is, the greater the potential for a harmonious marriage. A separation of property agreement must be made based on an agreement between the two parties so that no one feels disadvantaged. The marriage agreement must also be approved by an authorized official. This study uses the Normative Juridical approach method, namely legal research conducted by examining library materials or secondary data as a basis for research by conducting a search for regulations and literature related to the problems being studied